KEMAMPUAN KONEKSI MATEMATIKA BERDASARKAN GAYA KOGNITIF REFLEKTIF DAN IMPLUSIF (STUDI KASUS PADA SISWA KELAS VIII A SMP NEGERI 1 PALANG TUBAN) - Nofitasari, Yulia; Latifah, Eny (PHENOMENON : Multidisciplinary Journal Of Sciences and Research, 2025)
This study aims to analyze mathematical connection skills based on reflective and impulsive cognitive styles among eighth-grade students of SMP Negeri 1 Palang Tuban. The research employed a quantitative approach with a case study design. The results show that students with a reflective cognitive style are able to connect representations of concepts and procedures, reflect on the relationships among mathematical topics, and apply mathematics in daily life. They are also able to utilize connections across topics such as sequences, ratios, and geometry. However, reflective students are still less capable of understanding equivalent representations of the same concept, such as cube nets, and are weak in linking procedures for calculating the edges of large and small cubes using ratio concepts. Meanwhile, students with an impulsive cognitive style can demonstrate relationships between cubes and rectangular prisms and understand the connection between geometry and ratios. Nevertheless, they struggle to apply mathematics in daily life, have difficulty with equivalent representations, and tend to provide oral responses that are indecisive and easily influenced.